A Comparison of Leaf and Petal Senescence in Wallflower Reveals Common and Patterns of Gene Expression and Physiology - Price, Anna Marie; Orellana, Danilo F.; Mohd. Salleh, Faezah; Stevens, Ryan; Acock, Rosemary; Wollaston, VickyBuchanan; Stead, Anthony D.; Rogers, Hilary J. (American Society of Plant Biologists, 2008)

(untitled)
Petals and leaves share common evolutionary origins but perform very different functions. However, few studies have compared leaf and petal senescence within the same species. Wallflower (Erysimum linifolium), an ornamental species closely related to Arabidopsis (Arabidopsis thaliana), provide a good species in which to study these processes. Physiological parameters were used to define stages of development and senescence in leaves and petals and to align these stages in the two organs. Treatment with silver thiosulfate confirmed that petal senescence in wallflower is ethylene dependent, and treatment with exogenous cytokinin and 6-methyl purine, an inhibitor of cytokinin oxidase, suggests a role for cytokinins in this process. Subtractive libraries were created, enriched for wallflower genes whose expression is up-regulated during leaf or petal senescence, and used to create a microarray, together with 91 senescence-related Arabidopsis probes. Several microarray hybridization classes were observed demonstrating similarities and differences in gene expression profiles of these two organs. Putative functions were ascribed to 170 sequenced DNA fragments from the libraries. Notable similarities between leaf and petal senescence include a large proportion of remobilization-related genes, such as the cysteine protease gene SENESCENCEASSOCIATED GENE12 that was up-regulated in both tissues with age. Interesting differences included the up-regulation of chitinase and glutathione S-transferase genes in senescing petals while their expression remained constant or fell with age in leaves. Semiquantitative reverse transcription-polymerase chain reaction of selected genes from the suppression subtractive hybridization libraries revealed more complex patterns of expression compared with the array data